Age and the subjective importance of personal values. (April 2021) - Borg, Ingwer
Abstract: Previous research has shown that persons' ratings of the importance of personal values are correlated with age: The older the persons, the more they favor conservation-related values, and the less they prioritize stimulation and change. We here take a closer look at these findings and show with four large representative surveys using two value scales that (1) all basic personal values are essentially linearly related to age; (2) stimulation/hedonism and power/achievement values drop in importance with increasing age, tradition-related values become more important, and self-transcendence values remain essentially stable; (3) the subjective importance of security remains stable at a high level for all age groups; (4) the rated importance of a personal value depends on the value's components addressed by the measurement instrument; (5) gender has essentially no effect on the age-value relation.